Radar Observations of Arctic Bird Migration at the Northwest Passage, Canada - Gudmundsson, Gudmundur A.; Alerstam, Thomas; Green, Martin; Hedenström, Anders (ARCTIC, 2002)
Bird migration was recorded by tracking radar and visual observation at 23 sites in the region of the Northwest Passage, between Baffin Island and Herschel Island in the Beaufort Sea. The studies took place during a ship-based expedition from 29 June to 3 September 1999. A total of 692 tracks (average duration 160 s) of bird flocks on postbreeding migration were recorded. Eastward migration was widespread, with the highest intensities at three sites in the southeastern Beaufort Sea. Mainly shorebirds were responsible for these movements, migrating along routes similar to great circles towards Nova Scotia and other parts of the Atlantic coast of North America (whence they depart on transoceanic flights towards South America). Some of the birds in this migration system probably originated from Siberia, as indicated by high-altitude eastward migration at a site 100 km north of the coast in the Beaufort Sea. Another category of eastward migrants consisted of jaegers, terns, and red phalaropes traveling towards the Davis Strait region and into the Atlantic Ocean. Southward migration was recorded at Baffin Island. A westward migration was pronounced at King William Island (with simultaneous eastward migration) and Amundsen Gulf, while northward movements were important at Banks Island and Melville Island. Apart from westward moult migration of common eiders at Amundsen Gulf, the westward and northward tracks reflected mainly jaegers, terns, gulls, and red phalaropes. These birds were probably making northward flights to exploit pelagic food resources in waters where the ice had recently broken up before their westward migratory exodus from the Arctic region towards the Pacific Ocean. The mean altitude of migration was 793 m, with 27% of all tracks above 1000 m and a maximum height of 3.95 km. The altitude distribution was clearly lower than those of the corresponding migration in Siberia and the shorebird migration at Nova Scotia. The average ground speed (14.9 m/s) was only slightly faster than the mean air speed ...